Bovine Anaplasmosis: Will there ever be an almighty effective vaccine? - Salinas-Estrella, Elizabeth; Amaro-Estrada, Itzel; Cobaxin-Cárdenas, Mayra E.; Preciado de la Torre, Jesús F.; Rodríguez, Sergio D. (Frontiers in Veterinary Science, 2022)
Bovine anaplasmosis is a bacterial disease with a worldwide distribution and the cause of severe economic losses in the livestock industry in many countries including México. In the present work, we review first, the elements of the immune response which allows the bovine ameliorate the clinical signs while eliminating the majority of the blood forms and generating a immunologic memory such that future confrontations with the pathogen will not end in disease. On the other hand, many vaccine candidates have been evaluated for the control of bovine anaplasmosis yet without no commercial worldwide effective vaccine. Lastly, the diversity of the pathogen is reviewed and how this diversity has impaired the many efforts to control the disease.